Foreign Capital Inflows and Economic Growth in GCC Countries - Debbiche, Imene (International Journal of Economics and Financial Issues, 2020)
This paper provides a literature review and an empirical study of the particular independent growth impact of various capital inflows in the GCC countries during the period 2005-2018. It augments the standard growth determinants with inflows of foreign direct investment (FDI), foreign portfolio investment (FPI) and other investments (OI) and estimates this equation with the LSDV estimator. Main results are that capital inflows as a whole don’t exert any effect on economic growth. However, when it is decomposed in different inflows kinds, other investment and FDI don’t affect growth while foreign portfolio investment has a significant negative effect. Keywords: Capital flows, FDI, Portfolio investment, other investment, economic growth, GCC countries. JEL Classifications : F21, F32, F43 DOI: https://doi.org/10.32479/ijefi.10319